2014
DOI: 10.1017/s0022029914000582
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic effect of galactooligosaccharides in alloxan-induced diabetic rats

Abstract: IABETES is characterized by hyperglycaemia and elevated production of reactive oxygen species (ROS). Clove is full of natural antioxidants such as polyphenols and essential oils. The aim of the study was to investigate the hypoglycaemic effect of clove extract in diabetic rats. The results with test rats indicated that alloxan administration induced the elevation of glucose level, activity of some liver enzymes, malondialdehyde (MDA), urea and creatinine concentrations as well as the level of some lipid conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…The hypolipidemic effect of oat–bean cookies may be related also to their content of dietary fiber and galacto‐oligosaccharides, since SDF retards triglyceride and cholesterol intestinal absorption due to its high viscosity . SDF and galacto‐oligosaccharides have been reported to reduce triglyceride and cholesterol serum levels via the production of short‐chain fatty acids, which modulate hepatic lipid metabolism . Similarly, IDF has been reported to increase Foxa2 and Pgc‐1b expression, which concomitantly promote hepatic fatty acid β‐oxidation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypolipidemic effect of oat–bean cookies may be related also to their content of dietary fiber and galacto‐oligosaccharides, since SDF retards triglyceride and cholesterol intestinal absorption due to its high viscosity . SDF and galacto‐oligosaccharides have been reported to reduce triglyceride and cholesterol serum levels via the production of short‐chain fatty acids, which modulate hepatic lipid metabolism . Similarly, IDF has been reported to increase Foxa2 and Pgc‐1b expression, which concomitantly promote hepatic fatty acid β‐oxidation …”
Section: Discussionmentioning
confidence: 99%
“…28 SDF and galacto-oligosaccharides have been reported to reduce triglyceride and cholesterol serum levels via the production of short-chain fatty acids, which modulate hepatic lipid metabolism. 38 Similarly, IDF has been reported to increase Foxa2 and Pgc-1b expression, which concomitantly promote hepatic fatty acid -oxidation. 29 IF Pérez-Ramírez et al…”
Section: As Shown Inmentioning
confidence: 98%
“…Short‐chain fructooligosaccharides (scFOS) are fructooligosaccharides (FOS) with low degree of polymerization, and together with xylooligosaccharides (XOS) and galactooligosaccharides (GOS) are prebiotics that have not been much studied in fish (Dimitroglou et al., ; Merrifield, Dimitroglou, et al., ; Ringø et al., , ). In mammals, FOS, XOS and GOS were reported to improve glucose tolerance, by lowering plasma glucose levels and enhancing insulin sensitivity, and to reduce hepatic lipogenesis, plasma cholesterol and triglycerides levels (Fiordaliso et al., ; Gobinath, Madhu, Prashant, Srinivasan, & Prapulla, ; Sangwan, Tomar, Ali, Singh, & Singh, ; Shinoki & Hara, ; Vulevic, Juric, Tzortzis, & Gibson, ; Wang, Cao, Wang, & Sun, ). Prebiotic effects in fish intermediary metabolism are restricted to a few studies (Guerreiro, Enes, Merrifield, Davies, & Oliva‐Teles, ; Guerreiro, Enes, & Oliva‐Teles, ; Guerreiro, Oliva‐Teles, et al., ; Torrecillas et al., ; Torrecillas et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…triglycerides levels (Fiordaliso et al, 1995;Gobinath, Madhu, Prashant, Srinivasan, & Prapulla, 2010;Sangwan, Tomar, Ali, Singh, & Singh, 2015;Shinoki & Hara, 2011;Vulevic, Juric, Tzortzis, & Gibson, 2013;Wang, Cao, Wang, & Sun, 2011). Prebiotic effects in fish intermediary metabolism are restricted to a few studies (Guerreiro, Enes, Merrifield, Davies, & Oliva-Teles, 2015;Torrecillas et al, 2011;Torrecillas et al, 2015).…”
mentioning
confidence: 99%
“…It has been reported that lactose-based prebiotics, such as galacto-oligosaccharide (SANGWAN et al, 2015) and tagatose (ENSOR et al, 2015), reduce the long-standing elevated level of blood glucose (hyperglycemia). Several possible mechanisms have been published.…”
Section: Controlling Blood Glucose Levelmentioning
confidence: 99%